ANALISIS SWOT UNTUK PENENTUAN STRATEGI PEMASARAN PERUSAHAAN - Putra, Dzulfikar Dhiya Khairullah; Basuki, Ananto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Smolio Clothing is a fashion business MSME that has a child-like concept with fun, pop and colorful themes. This study aims to describe the internal and external environmental conditions of marketing and determine the right strategy for developing Smolio Clothing's fashion business in Indonesia. This research uses a descriptive qualitative research type. The problem analysis method used is SWOT analysis (Strengths, Weakness, Opportunity, Threats) and QSPM (Quantitative Strategic Planning Matrix) matrix. The results of this study indicate that the marketing conditions of the Smolio Clothing business in the IE Matrix are in quadrant II, with a grow and build strategy. Of the 11 alternative strategies formulated using the SWOT matrix, based on the results of the QSPM matrix, the right strategy to use is an intensive type of strategy in the form of market penetration with a TAS of 6.45. The strategies that Smolio Clothing can implement are conducting better marketing activities to increase brand trust, selling through various social e-commerce platforms that have sprung up, making products with new types and variants, looking for alternative suppliers to lower costs and selling.